2022
DOI: 10.3389/fgene.2022.850195
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive gene expression patterns in pregnancy-associated breast cancer

Abstract: Pregnancy-associated breast cancer (PABC) is diagnosed during pregnancy or within 1 year postpartum, but the unique aspects of its etiology and pathogenesis have not been fully elucidated. This study aimed to ascertain the molecular mechanisms of PABC to facilitate diagnosis and therapeutic development. The Limma package was used to characterize the differentially expressed genes in PABC as compared to non-pregnancy-associated breast cancer (NPABC) and normal breast tissue. A total of 871 dysregulated genes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…( 21 )observed that among a cohort of 20 PABC patients, 35% of PABC patients tested carried pathogenic mutations in BRCA1 and CHEK2 genes. Some patients carrying germline mutations did not report a family history of cancer ( 21 ).Thus, highlighting the genomics of PABC and examining all biological pathways will further facilitate the identification of novel biomarkers defining women who are at high risk of developing PABC in the general population ( 18 , 22 ). BC-PP is also more unfavorable, as the rate of HER-2 positive and Ki-67≥20% was significantly higher than that of its controls (P=0.01, 0.018, respectively), although age, year of diagnosis, and TNM stage were well matched.…”
Section: Discussionmentioning
confidence: 99%
“…( 21 )observed that among a cohort of 20 PABC patients, 35% of PABC patients tested carried pathogenic mutations in BRCA1 and CHEK2 genes. Some patients carrying germline mutations did not report a family history of cancer ( 21 ).Thus, highlighting the genomics of PABC and examining all biological pathways will further facilitate the identification of novel biomarkers defining women who are at high risk of developing PABC in the general population ( 18 , 22 ). BC-PP is also more unfavorable, as the rate of HER-2 positive and Ki-67≥20% was significantly higher than that of its controls (P=0.01, 0.018, respectively), although age, year of diagnosis, and TNM stage were well matched.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences are also detected regarding gene expression patterns in breast tumors detected in patients with PABC and non-pregnancy-associated breast cancer [ 35 ]. PABC epithelial cells have additional copy numbers of DNA coding genes for morphogenesis, angiogenesis and metastases, as well as fewer copy numbers of DNA coding genes for tumor suppressors, cell adhesion, macromolecular complex assembly, and intra-cellular trafficking, changes that accumulatively lead to increased invasiveness and biological aggressiveness [ 25 , 27 ].…”
Section: Pathophysiological Biological and Molecular Basis Of Pabcmentioning
confidence: 99%